2021
DOI: 10.1073/pnas.2018220118
|View full text |Cite
|
Sign up to set email alerts
|

The zebrafishgrimemutant uncovers an evolutionarily conserved role for Tmem161b in the control of cardiac rhythm

Abstract: The establishment of cardiac function in the developing embryo is essential to ensure blood flow and, therefore, growth and survival of the animal. The molecular mechanisms controlling normal cardiac rhythm remain to be fully elucidated. From a forward genetic screen, we identified a unique mutant, grime, that displayed a specific cardiac arrhythmia phenotype. We show that loss-of-function mutations in tmem161b are responsible for the phenotype, identifying Tmem161b as a regulator of cardiac rhythm in zebrafis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 52 publications
2
17
1
Order By: Relevance
“…We observed that the AP duration in atrial CMs was shorter than in RV CMs, similar to isolated human primary CMs (Figures 4I and 4L,S4H,and S4I). Furthermore, the diastolic potential was around -70 mV (Figures 4J), closer to in vivo CMs than most other iPSC-derived systems (Verkerk et al, 2021). In addition, the upstroke velocity (Figure S4J) and amplitude (Figure 4K) of the action potentials resembled other in vitro models.…”
Section: Functional Characterization Of the Five Cardioid Subtypessupporting
confidence: 55%
See 1 more Smart Citation
“…We observed that the AP duration in atrial CMs was shorter than in RV CMs, similar to isolated human primary CMs (Figures 4I and 4L,S4H,and S4I). Furthermore, the diastolic potential was around -70 mV (Figures 4J), closer to in vivo CMs than most other iPSC-derived systems (Verkerk et al, 2021). In addition, the upstroke velocity (Figure S4J) and amplitude (Figure 4K) of the action potentials resembled other in vitro models.…”
Section: Functional Characterization Of the Five Cardioid Subtypessupporting
confidence: 55%
“…We also investigated how calcium transits across the whole cardioid; we found that the LV cardioid has a prolonged transient compared to atrial and AVC cardioids (Figures S4C, S4D, S4E, and S4F) as reported in vivo (Koopman et al, 2021). In addition, the speed of signal propagation across cardioids differed between cardioid types and differentiation stages, where the LV cardioid's calcium transients propagated faster (180.3 um/ms) than both the atrial (111 um/ms) and AVC cardioids (52.48 um/ms) (Figures 4F and 4G).…”
Section: Functional Characterization Of the Five Cardioid Subtypesmentioning
confidence: 82%
“…In all KOs examined, in gross (n > 50), as well as on microCTs (n = 8), no limb or digit abnormalities, renal cysts, or grossly apparent skeletal dysplasia were observed ( 29 , 31 ). We did see previously described cardiac hypertrophy ( 16 ). Together, the gross phenotypes of the Tmem161b KO mouse imply a CNS-specific deficiency in normal Shh signaling, but no signs of Shh signaling defects or ciliopathy in tissues where developmental Tmem161b expression is low.…”
Section: Resultsmentioning
confidence: 99%
“…Here, we identify individuals with variants in TMEM161B with diffuse polymicrogyria (PMG)—a disorder of cortical gyration—but with limited extra-CNS manifestations of disease. At the outset of our work, no biological functions had been ascribed to TMEM161B, although it was recently identified as a regulator of cardiac rhythm by tempering specific currents ( 16 ). TMEM161B belongs to a superfamily of proteins conserved down to single-celled eukaryotes, with unknown biochemical functions.…”
mentioning
confidence: 99%
“…Notably, none of the heart atrial appendage eQTLs we identified have been previously associated with cardiac health or atrial fibrillation by GWAS (GWAS catalog, November 2, 2021 ). However, the genes on the opposite strands to the two antisense genes (i.e., TMEM161B-AS1 and KANSL1-AS1 ) have been previously implicated in regulating cardiac rhythm with zebrafish model (i.e., TMEM161B ( Koopman et al, 2021 )) and congenital heart defects in humans (i.e., KANSL1 ( Koolen et al, 2016 ; León et al, 2017 )). However, there is a growing body of research indicating a close relationship between cardiovascular health and PD development ( Awerbuch and Sandyk, 1994 ; Ascherio and Tanner, 2009 ; Fang et al, 2018 ; Scorza et al, 2018 ; Hong et al, 2019 ; Potashkin et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%